1999
DOI: 10.1021/ie980455l
|View full text |Cite
|
Sign up to set email alerts
|

Computational Strategies for Sizing Liquid−Liquid Extractors

Abstract: A stagewise model is presented for the design of countercurrent liquid−liquid extraction columns allowing for breakage and coalescence. Backflow in the continuous phase is considered, and the nonideal behavior of the dispersed phase is described in terms of the drop-size distribution and individual drop velocities. The drop-size distribution, and dispersed-phase holdup are determined along the column. The model is applicable for any equilibrium relationship and allows for the variation in the physical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
0
21
0
3
Order By: Relevance
“…Several correlations for rigid drops are described in the literature [2]. However, in this work, only the most recent ones have been implemented in the code, which is capable of selecting the most appropriate of them according to criteria expressed in terms of dimensionless numbers such as Pe c , Re and Sc.…”
Section: Correlations For Rigid Dropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several correlations for rigid drops are described in the literature [2]. However, in this work, only the most recent ones have been implemented in the code, which is capable of selecting the most appropriate of them according to criteria expressed in terms of dimensionless numbers such as Pe c , Re and Sc.…”
Section: Correlations For Rigid Dropsmentioning
confidence: 99%
“…Several correlations and models are reported in the literature for the case of oscillating drops [2], and no specific conditions are imposed for their use. Therefore in this work, the Garner correlation, has been chosen and is expressed as follows: …”
Section: Correlations For Oscillating Dropsmentioning
confidence: 99%
“…However, due to the complex nature of the extraction process, the design procedures and practices (correlations) are not yet well established and usually pilot scale testing is required for such columns. Although some advanced modeling techniques [29][30][31][32][33][34] are currently acclaimed, however, for the reliable design strategies and computer methods to be well developed, more of such experimental studies (relationships among the column efficiency and operating parameters) on a pulsed sieve-plate column have to be accomplished for the various geometries and liquidliquid systems. The review of the literature suggests that the dispersed phase holdup and mass transfer performance are generally studied for short columns with a few number of plates and with plate free area greater than 19%.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Some authors found that E d is of an order of magnitude less than E c and does not affect their results. [19,20] So, studies on nonideal PDDC factors traditionally focused on the axial mixing performance of the continuous phase (E c ), which is correlated with experimental parameters at different conditions. Some literature correlations results are listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%